Male-produced sex attractant pheromone of the green stink bug, Acrosternum hilare (Say) - MCBRIEN, Heather L; MILLAR, Jocelyn G; GOTTLIEB, Levi; XIN CHEN; RICE, Richard E (Journal of chemical ecology, 2001)
Sexually mature virgin adult males of the green stink bug, Acrosternum hilare attracted sexually mature virgin adult females in laboratory bioassays using a vertical Y-tube. There was no indication that males attracted other males, or that females attracted either sex. These results suggested that A. hilare males produce a sex pheromone. Extracts of odors collected from sexually mature males contained compounds that were not present in extracts from females or sexually immature males. (4S)-Cis-(Z)-bisabolene epoxide ((4S)-cis-Z-BAE) was the major sex-specific component of the extract. The crude extract was attractive to female A. hilare, but when separated into four fractions, only the portion containing (4S)-cis-Z-BAE and the minor component (4S)-trans-Z-BAE was attractive to females. This fraction was as attractive as the crude extract, suggesting that the former contained all the pheromone components. Neither synthetic (4S)-cis-Z-BAE nor (4S)-trans-Z-BAE alone was attractive to females, but a 95:5 cis:trans blend, mimicing the ratio naturally produced by males, was attractive to females in Y-tube bioassays. Bioassays in a field cage showed that significantly more A. hilare females were attracted to cotton string lures treated with 1 mg of a 95:5 blend of (4S)-cis-Z-BAE and (4S)-trans-Z-BAE placed inside a bouquet of alfalfa than to an alfalfa bouquet containing a pentane-treated control. In field cage studies, attraction of females was greatest during the late afternoon and evening hours, and female A. hilare approached the synthetic pheromone source almost exclusively by walking.